Karakteristik perpindahan panas pada kolektor sinar matahari tipe plat datar - Sekarwati, Aulifia Krisna Cahya (Maliki Interdisciplinary Journal, 2026)
This study aims to investigate the heat transfer characteristics and efficiency of a flat-plate solar collector under various experimental conditions. The experiments were conducted using a halogen lamp as an artificial radiation source to simulate solar irradiation. Several variations were applied, including a complete collector and a collector without a glass cover, different inlet water temperatures, and the effect of forced air flow generated by a blower on the collector surface. The measured parameters included inlet and outlet water temperatures, ambient temperature, and fluid flow rate. The collector efficiency was determined by comparing the useful heat gained by the working fluid to the incident radiation energy received by the collector. The results indicate that the presence of a glass cover reduces heat losses to the environment and improves collector efficiency. An increase in inlet water temperature and the application of cold air flow on the collector surface tend to decrease efficiency due to enhanced convective heat losses. This study provides insight into the influence of operational conditions and collector configuration on the heat transfer characteristics of flat-plate solar collectors.